1996
DOI: 10.1080/15216549600201272
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of estradiol-17β secretion in ovarian granulosa cells by an extract from the submandibular gland of the rat

Abstract: The submandibular salivary gland (SMG) in the rodent is a rich source of growth factors. The estradiol-17[~ (E2) secretions were studied in the primary cultures of ovarian granulosa cells from sialoadenectomized (surgical removal of SMG, SDX) immature rats. The secretions of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were also studied in the primary cultures of anterior pituitary cells from SDX rats. E2 secretion from the ovarian granulosa cells of SDX rats was not affected by male and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Combining these results with previous findings that SMG extract did not affect the secretion of LH and FSH by anterior pituitary cells, with or without the presence of luteinizing hormonereleasing hormone (LH-RH) [23] , it is concluded that a direct effect of the LH action is…”
Section: Biochemistry Ond Molecular Biology Internationalsupporting
confidence: 49%
“…Combining these results with previous findings that SMG extract did not affect the secretion of LH and FSH by anterior pituitary cells, with or without the presence of luteinizing hormonereleasing hormone (LH-RH) [23] , it is concluded that a direct effect of the LH action is…”
Section: Biochemistry Ond Molecular Biology Internationalsupporting
confidence: 49%